Full-Wave Simulation of Body Absorption due to Radiated Fields at GHz Frequencies - Carballo-Madrigal, Jose Alberto (2018)
Exposition of humans to non-ionizing radiation at high frequencies has become ubiquitous due to the higher number of systems operating in that frequency range such as cell phones, wireless networks, and communication systems. The modeling of the impact of this type of radiation is an important issue due to potential short and long-term health effects and for the establishment of regulatory safety limits. From the simulation point of view, this is a challenging task since the wavelengths of interest are much smaller than the typical dimensions of a human body, which leads to the requirement of very fine discretization of the geometrical models and the consequent high demand of computational resources and long execution times.This article studies the feasibility of a full-wave simulation of field absorption at high frequencies, up to 10 GHz, with general purpose numerical methods and geometries with sizes in the order of a human body. Simple geometries are analyzed, assuming the material properties of fresh water for their inner region. Three different methods are evaluated: the finite integration technique (FIT), finite element method (FEM), and method of moments (MoM), to determine the result convergence and required computational resources for each solution. The results show that already at 10 GHz it is difficult to perform the analysis with moderate computational power (up to 64 GB RAM), but some approximations might be exploited since field penetration in that frequency range is mostly limited to the surface region.